Innovation of Pedagogy: Development of Digital Classroom to Increasing Student’s In Foreign Language Profiency - Uci Dwi Cahya (Universitas Lancang Kuning, 2023)
This study aims to develop a digital classroom to improve the foreign language skills of MA MUQ Langsa students in facing digital-based learning challenges according to the demands of the 21st century. To find out the effectiveness of using digital classes in foreign language learning. The method in this study is the research and development (R&D) method. The results of this study were testing foreign language learning materials with a score of 4.00 (good category) and media testing with media experts obtained a score of 4.00 (good category). Meanwhile, for random testing of students, a score of 4.00 (good category) was obtained. The average score obtained at the pretest was 38.88 and the posttest was 39.00. So that it can be explained from the results of alpha and beta testing and seeing the effectiveness of product development, it can be concluded that the product is feasible and effective for learning foreign languages. This of course will be very beneficial for teachers in transferring teaching materials and providing innovation in student learning spaces.